(untitled) (Balneo and PRM Research Journal, 2024)
Low back pain (LBP) is a common medical condition with a negative impact on quality of life and work. It also leads to financial costs for the health system by increasing the costs of medical treatment. Numerous studies have focused on the effects of exercise, with some highlighting the role of protective studies in LBP while other studies have shown no beneficial. There is moderate-certainty evidence that therapeutic exercise is beneficial in the treatment of chronic low back pain compared with other treatment modalities. Muscle strengthening and the creation of spinal mobility through specific exercise is a recognized therapeutic approach to the prevention and treatment of LBP. The main objecvtive is to evaluate the effectiveness of a physi-cal therapy program utilizing the 360 Huber platform on the quality of life for individuals with chronic lumbar radiculopathy. A randomized controlled trial was conducted with 30 participants diagnosed with chronic lumbar radiculopathy. Participants were divided into an ex-perimental group (n=20) receiving the 360 Huber platform-based rehabilitation protocol, and a control group (n=10) continuing standard care. The intervention included 15 sessions of physical therapy on the 360 Huber platform, complemented by electrotherapy and therapeutic massage. The Oswestry Disability Index (ODI) was administered pre- and post-intervention to assess changes in functional outcomes and quality of life. The experimental group demonstrat-ed a significant reduction in ODI scores, with an average decrease of 1.85 points (10.11%) from 18.30 to 16.45. The paired t-test analysis revealed a statistically significant difference (p < 0.001) and a very large effect size (1.11), indicating substantial improvements in functional outcomes. The control group showed no significant changes. The rehabilitation protocol using the 360 Huber platform, combined with electrotherapy and therapeutic massage, effectively im-proves functional outcomes and quality of life for patients with chronic lumbar radiculopathy. The study highlights the potential of integrating advanced technology with traditional physical therapy methods to enhance treatment efficacy. Future research with larger sample sizes and longer follow-up periods is recommended to confirm these findings and explore additional therapeutic modalities.